O lugar do marxismo de Frantz Fanon e Caio Prado Júnior: o pensamento revolucionário na periferia do sistema capitalista - D’Agostini, Maria Stella Martins Silva (2019)
This work talks about the revolutionary praxis of two thinkers: the Brazilian Caio Prado Júnior and the martinicano Frantz Fanon. Both of then used marxism, thinking the tactics and particular strategies of marxism in these two countries, Brazil and Argelia. This study pretends to think about the political thoughts and actions of these intelectuals, including an analysis of their trajectories; thesis; interlocution; historic, social and political contexts, what skills the diagnosis and prescriptions of their revolutionary practices in the fights to socialism. This efforts of thinking about the thoughts of Fanon and Prado Júnior, evolve the identification of the elective affinities of their ways. This should make the elements what a system of classification of both intellectuals viable; a line of marxism in the political thinkers developed in the periphery of capitalism.